2020
DOI: 10.1108/jfm-06-2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the role of facilities management in the fight against the COVID-19 (SARS-CoV-2) pandemic in developing countries’ public hospitals

Abstract: Purpose This paper aims to present a review of the current COVID-19 pandemic with particular emphasis on developing countries in Africa. It aims to demonstrate how facilities management (FM) services delivery in public hospitals can be improved for the fight against the COVID-19 pandemic. Design/methodology/approach This paper embraces a review of current literature on COVID-19 and FM together with credible media updates. The paper critically synthesizes knowledge on the pandemic to position a technical view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Healthcare services, including hospitals, are considered a fundamental infrastructure of every country [1]. With the recent outbreak of the COVID-19 pandemic, the design of healthcare facilities (or healthcare architecture) has become one of the top priorities for healthcare policy makers as the design of the hospital can lead to positive patient health outcomes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare services, including hospitals, are considered a fundamental infrastructure of every country [1]. With the recent outbreak of the COVID-19 pandemic, the design of healthcare facilities (or healthcare architecture) has become one of the top priorities for healthcare policy makers as the design of the hospital can lead to positive patient health outcomes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, developing an automated, flexible work scheduling system and facilitating the work-from-home to optimize FM staff's physical presence in the healthcare can reduce the total number of internal staff inside the building [16]. On the other hand, Amos et al (2020) suggested that continuously updated training for the FM staff who work in the healthcare sector about the new diseases and infections prevention will integrate the power of the FM knowledge with the medical science, which in summary will contribute in providing fast responses for any future pandemics [11].…”
Section: Literature Review a Importance Of Facility Management In Healthcarementioning
confidence: 99%
“…Regardless of the phase of the pandemic, facilities offering mission critical services are in operation. FM plays an important role because it ensures that these facilities are operating efficiently to fight against COVID-19 (Amos et al , 2021). On the other hand, lockdowns may lead to full or partial shutdown of less critical buildings and a reduction in services, leading to a scaling back on FM operations (Rashdi et al , 2020).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Apart from healthcare workers, facility management professionals (FMPs) and operatives (collectively known as FM staff) are also among the essential workforce on the front line of the pandemic as they need to meet the heightened demand to provide a clean, healthy, safe and sustainable environment (IFMA Foundation, 2020). FM plays an important role to ensure that the facilities are operational and safe during the pandemic (Amos et al , 2021).…”
Section: Introductionmentioning
confidence: 99%